The effect of biomass-water ratio on bio-crude oil production from Botryococcus braunii using hydrothermal liquefaction process - Laras Prasakti; Rochmadi Rochmadi; Arief Budiman (Jurnal Rekayasa Proses, 2019)
The increasing demand of energy in Indonesia has led to the urgency to conduct research and development in renewable energy. Biomass is one of the largest renewable energy sources in Indonesia. For biomass to energy conversion, hydrothermal liquefaction (HTL) has been considered as one of the potential methods where biomass is processed using subcritical water to produce bio-oil, aqueous phase, gas, and solid product. In this research, the effect of biomass-water ratio on hydrothermal liquefaction (HTL) process of microalgae Botryococcus braunii has been investigated. The HTL was conducted using biomass/water ratio 1:10, 1:20 and 1:30 with various holding time for each ratio. The product was bio-crude oil with similar characteristics to crude oil. Experimental results showed that biomass-water ratio affected the distribution of bio-crude oil yields. For biomass-water ratio of 1:10 and 1:20, it was found that bio-crude oil yields reached a maximum at 20 minutes, while the highest bio-crude oil yield of 4% was obtained at biomass-water ratio of 1:10. On the other hand, with biomass-water ratio of 1:30, bio-crude oil yield was continuously increasing with holding time until it reached the maximum yield of 4% at 40 minutes of holding time. The aforementioned results indicated that the highest bio-crude oil yield was obtained using biomass-water ratio 1:10 and 20 minutes of HTL processing time.